WATER MASS DYNAMICS IN AMBON BAY - Frilla Renty Tama Saputra; Yohanis Dominggus Lekalette (Pusbindiklat - LIPI, 2016)
Ambon Bay has a unique characterictic with its semi enclosed water inner bay. The aim of this research is to study the dynamics of water mass in Ambon Bay through the observation of vertical and horizontal distribution of temperature and salinity. The observation was conducted in 18 different stations throughout 2015 during Northwest Monsoon (February), Transition I (April), Southeast Monsoon (August), and Transition II (November). The result shows that the dynamics of water masses in Ambon Bay is strongly influenced by the monsoon. During the Northwest Monsoon, the temperature is higher than the other season and mixing phenomenon occurs, which is caused by heat diffusion from the surface. In the Transition I, water column stratification tends to occur caused by its mixing with fresh water. In Southeast Monsoon, the temperature in Ambon Bay is lower than the other season and flushing phenomenon occurs in Inner Ambon Bay which is caused by high density water mass flow from Banda Sea to Inner Ambon Bay. Entering the Transition II, the temperature are getting warmer again and forming a stratification which is caused by heat diffusion from the surface. The salinity profile in Ambon Bay shows the similar characteristic with temperature in every season. The salinity in Inner Bay is lower than the Outer Bay due to its mixing with fresh water.